Differential immunostaining patterns of transient receptor potential (TRP) ion channels in the rat nodose ganglion - Jawaid, Safdar; Herring, Amanda I; Getsy, Paulina M; Lewis, Stephen J; Watanabe, Michiko; Kolesova, Hana (Journal of anatomy, 2022)
Vagal afferents regulate numerous physiological functions including arterial blood pressure, heart rate, breathing, and nociception. Cell bodies of vagal afferents reside in the inferior vagal (nodose) ganglia and their stimulation by various means is being considered as a way to regulate cardiorespiratory responses and control pain sensations. Stimulation of the nodose by exposure to infrared light is recently being considered as a precise way to elicit responses. These responses would likely involve the activity of temperature-sensitive membrane-bound channels. While papers have been published to track the expression of these transient receptor potential ion channels (TRPs), further studies are warranted to determine the in situ expression of the endogenous TRP proteins in the nodose ganglia to fully understand their pattern of expression, subcellular locations, and functions in this animal model. TRP ion channels are a superfamily of Na+ /Ca2+ -channels whose members are temperature- and/or mechano-sensitive and therefore represent a potential set of proteins that will be activated directly or indirectly by infrared light. Here, we report the spatial localization of six TRP channels, TRPV1, TRPV4, TRPM3, TRPM8, TRPA1, and TRPC1, from nodose ganglia taken from juvenile male Sprague-Dawley rats. The channels were detected using immunohistology with fluorescent tags on cryosections and imaged using confocal microscopy. All six TRP channels were detected with different levels of intensity in neuronal cell bodies and some were also detected in axonal fibers and blood vessels. The TRP receptors differed in their prevalence, in their patterns of expression, and in subcellular expression/localization. More specifically, TRPV1, TRPV4, TRPA1, TRPM8, TRPC1, and TRPM3 were found in vagal afferent cell bodies with a wide range of immunostaining intensity from neuron to neuron. Immunostaining for TRPV1, TRPV4, and TRPA1 appeared as fine particles scattered throughout the cytoplasm of the cell body. Intense TRPV1 immunostaining was also evident in a subset of axonal fibers. TRPM8 and TRPC1 were expressed in courser particles suggesting different subcellular compartments than for TRPV1. The localization of TRPM3 differed markedly from the other TRP channels with an immunostaining pattern that was localized to the periphery of a subset of cell bodies, whereas a scattering or no immunostaining was detected within the bulk of the cytoplasm. TRPV4 and TRPC1 were also expressed on the walls of blood vessels. The finding that all six TRP channels (representing four subfamilies) were present in the nodose ganglia provides the basis for studies designed to understand the roles of these channels in sensory transmission within vagal afferent fibers and in the responses elicited by exposure of nodose ganglia to infrared light and other stimuli. Depending on the location and functionality of the TRP channels, they may regulate the flux of Na+ /Ca2+ -across the membranes of cell bodies and axons of sensory afferents, efferent (motor) fibers coursing through the ganglia, and in vascular smooth muscle.
Keywords: autonomic nervous system; Animals; nodose ganglion; kationtové kanály TRPV; TRPC1; TRPV1; ganglion inferius; TRPM Cation Channels; Nodose Ganglion; immunohistochemistry; kationtové kanály TRPM; TRPV Cation Channels; Transient Receptor Potential Channels; blood vessels; Rats, Sprague-Dawley; vagus nerve; TRPA1; nervus vagus; Male; potkani Sprague-Dawley; TRPM8; krysa rodu Rattus; confocal microscopy; Vagus Nerve; TRPM3; mužské pohlaví; zvířata; TRPV4; Rats; kationtové kanály TRP